Nexus thinking as a force for peace - McCartney, Matthew P.; Ringler, Claudia (CGIAR System Organization, 2024)
The theme of this year’s World Water Day, celebrated on March 22, was ‘Water for Peace’. This was echoed by the theme of the just-concluded World Water Week on ‘Bridging Borders: Water for a Peaceful and Sustainable Future’; the shared focus could not come at a more opportune time. Global water, food, and humanitarian crises have reached near-unprecedented levels. Because water is essential to life and livelihoods, its absence is a crisis multiplier – an underlying factor contributing to and compounding conflict and humanitarian crises. But this also means that improving water management can reduce the potential for conflict – and when conflict occurs, help to ease its impacts. NEXUS Gains implements research in countries suffering from severe water, energy, and food insecurity and environmental degradation. We had the opportunity to showcase several research results and innovations at World Water Week, including solutions to water shortages, next-generation datasets, real-time monitoring tools, and active groundwater management approaches.